El murmullo de la circulación de la sangre: la fotografía como medio narrativo en Educación Artística - Mesías Lemas, José María (Arte, Individuo y Sociedad, 2008)
This article proposes a reflection regards to the use of photography in Art Education from the Narrative-Art Research position and, particularly, from the Photo-Based Research approach. It explains a photography project developed with students from the University of Santiago de compostela, and manifest the practice application about the arguments to exposed in this paper.